Evaluation of Dermatology Treatment Satisfaction towards Hospital Reputation among Chronic Skin Disease Patients at An Eastern Indonesian Referral Hospital - Shienty Gaspersz; Ferdi Antonio; Paulus Mario Christopher (Asia Pacific Journal of Health Management)
Introduction: Chronic skin disease poses a major challenge due to the complexity of these diseases and the variety of symptoms require a highly individualized approach to diagnosis and long-term treatment. This study aimed to evaluate the factor of treatment satisfaction moderated with recurrency towards hospital reputation among patients with chronic skin disorder utilizing the modified Dermasat questionnaire with six variables (treatment effectiveness, convenience of use, impact on daily living, medical care information, treatment side effect tolerable) and an additional variable (physician communication).